Knowledge, Attitude, and Practice of Nurses Toward the Initial Managements of Acute Poisoning in Public Hospitals of Bahir Dar City, Northwest Ethiopia 2022: Cross-Sectional Study - Ousman Adal; Yigremew Hiamanot; Abdulkadir Zakir; Redeat Regassa; Asnake Gashaw (SAGE Publishing, 2023)
Introduction Poisoning is a common cause of medical visits and hospitalizations around the world. The knowledge, attitude, and practice of nurses in the management of acute poisoning are very poor in developing countries, such as Ethiopia. According to the previous study, 75% and 45% of nurses had unsatisfactory knowledge and practice, respectively. Objectives This study aimed to assess the knowledge, attitude, and practice of nurses toward the initial management of acute poisoning. Method An institution-based cross-sectional study design was used to recruit 422 nurses from public hospitals of Bahir Dar city in Ethiopia. A systematic random sampling method and an English version of self-administered questionnaires were used to collect the data. The data were entered into Epi Data and analyzed using SPSS version 25. Results The study recruited 422 nurses, with a response rate of 100%; 248 (58.8%) and 264 (62.2%) of the nurses had good knowledge and practice, respectively. Slightly more than half (57.6%) of the nurses had a positive attitude. Nurses who worked in an emergency and intensive care unit had twice the odds of having more knowledge and practice than those who worked in an outpatient department (AOR = 2.1, CI: (1.019, 4.540), p  = 0.001). Nurses who have MSc degree were twice (AOR = 2.1, CI: (1.019, 4.540), p  = 0.001) and three times (AOR = 3.1, CI: (1.012, 7.140), p  = 0.002) to have good knowledge and practice than those who have a diploma. Conclusion Slightly more than half of nurses had good knowledge, practice, and a positive attitude. Educational status, working in an emergency department, and having training in poison management have been significantly associated with the knowledge and practice of nurses. The authors recommended that there is a need to empower the attitude, knowledge, and practice of nurses through consistent training, accessing, and updating guidelines (poisoning management protocol). The author also suggested that the poison management protocol be incorporated into the Ethiopian nursing curriculum (certificates).